APLIKASI RENEWAL REWARD(Studi Kasus: Proses Renewal Reward pada Transaksi di Mixue Jimbaran) - Ni Putu Desy Susilawati; Komang Agus Mahendra Apriana; Putu Ayu Liana Prasetya Dewi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
A stochastic process is a probability model that describes a series of events occurring randomly within the context of specific conditions or time intervals. Stochastic processes are divided into two types, namely discrete stochastic and continuous-time stochastic. One example of discrete- time stochastic is the renewal process, which is a computational process where the time intervals between arrivals are independent and have an identical distribution (IID) with any distribution. One specific type of renewal process is applied in the context of queues and involves rewards, also known as the renewal reward process. This article aims to demonstrate that one of the transactions at the Mixue company located in Jimbaran, Bali, near the Polytechnic of Bali (PNB), fulfills the characteristics of the renewal reward process. The characteristics of the renewal ????(????) ????[????] ????[????(????)] ????[????] reward process that need to be met include the probability values ???? →????[???? ] dan ???? → ????[????] ????(????) ????[????] ????[????(????)] ????[????] To obtain the values of ????→????[???? ] dan  ???? → , this article utilizes secondary data obtained  ????[????] from the Mixue Jimbaran administration. After processing the data, the results show that the ????(????) ????[????(????)] ????[????] values of = ????????195.067 per unit time, ???? ???? = ????????195.066,667 per unit time, and ????[????] = ????????210.000 per unit time. From these results, it can be concluded that one of the transactions at Mixue, located in Jimbaran, satisfies the characteristics of the renewal reward process